Model Layanan Pendidikan Bagi Anak Berkebutuhan Khusus Yang Mengalami Kecacatan Fisik - Naura Azifa; Putri Adillah; Deta Rehulina; Wismanto Wismanto; Asyraf Hibatullah (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
Education is one of the efforts made to improve the quality of Indonesian human resources. Education can be obtained through formal, informal and non-formal educational institutions. This research was motivated by various cases that occurred related to the limited education received by children with special needs, and quite a few of these children even experienced discriminatory treatment. This research aims to reveal the characteristics of children with special needs who experience physical disabilities and educational service models that can be developed so that children with special needs obtain their educational rights. The research method is descriptive qualitative with data collection techniques in the form of literature studies from various references relevant to the symptoms observed. The collected data was analyzed descriptively qualitatively so that variations in the characteristics and models of educational services for children with special needs could be seen. The results of the research show that basically there are two categories of children with special needs, namely children with special needs who are temporary (temporary), namely learning obstacles caused by external factors such as trauma experienced in previous events and children with special needs who are permanent (permanent), namely learning obstacles that caused by internal factors such as a direct result of the disability experienced. The forms of services that can be taken for children with special needs are the form of segregated education services and the form of unified or integrated education services.